Does more cash in conditional cash transfer programs always lead to larger impacts on school attendance? - Filmer, Deon; Schady, Norbert (Elsevier, 2022)
There is considerable evidence that conditional cash transfer (CCT) programs can have large impacts on school enrollment, including in very poor countries. However, little is known about what features of program design account for the observed outcomes. In this paper we analyze the impact of a program in Cambodia that made payments of varying magnitude to otherwise comparable households. The identification is based on a sharp regression discontinuity design. We find that a modest cash transfer, equivalent to approximately 2 percent of the consumption of the median recipient household, had a substantial impact on school attendance, approximately 25 percentage points. A somewhat larger transfer did not raise attendance rates above this level.